A Novel Nocturnal Cooling Radiator Used for Supplemental Heat Sink of Active Cooling System. (2015) - Man, Yi; Yang, Hongxing; Qu, Yunxia; Fang, Zhaohong
Abstract: Nocturnal cooling radiation is one of the effective natural passive cooling technologies by infrared radiation exchange between terrestrial surfaces and the sky. Although the application of nocturnal cooling radiation technology as the exclusive heat sink in active cooling systems is inherently limited, it can be used as an excellent supplemental heat sink and to be activated under ideal meteorological conditions to reduce system energy consumption. A novel nocturnal cooling radiator (NCR) works as supplemental heat rejecter of active cooling system is designed in this study. A practical analytical model of the NCR is developed. A computer program based on this developed model is plotted and verified by experiment. Based on performance simulation results of a NCR operated in humid subtropical climate, the novel NCRis found to be feasible as the supplemental heat sink of active cooling system.